INVESTIGATION OF PHARMACOGNOSTICAL, PHYTOCHEMICAL, AND PHARMACOLOGICAL ACTIVITY OF AERIAL ROOTS OF FICUS BENGHALENSIS LINN - Mazumder, Kamalika; Maji, Himangshu S; Bala, Nripendra N (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Ficus benghalensis Linn. (Moraceae family) is commonly known as banyan tree in English, which is used traditionally in India. The literature survey showed that the aerial roots of this plant are yet to be explored. Our main interest is to evaluate its pharmacognostic and phytochemical character by the standard monograph and to explore its in vitro antioxidant and in vivo analgesic activity study with ethyl acetate extract. Methods: Pharmacognostic evaluation and phytochemical screening have been done using standard monograph. An in vitro antioxidant activity using ethyl acetate extract has been done using four different methods. In vivo analgesic activity of the ethyl acetate extract has been evaluated by acetic acid-induced writhing test in mice and tail flick method. Results: Aerial roots of F. benghalensis have been found the rich source of steroidal glycosides, cardiac glycosides, flavonoids, tri-terpenoids, and phenols. The presence of phellem, phellogen, xylem, and phloem has been found after microscopic investigation. All the pharmacognostic parameters proved its purity. Results showed the absence of heavy metals. The ethyl acetate extract has shown potent antioxidant activity at 100 Î¼g/ml concentration and higher analgesic activity at the concentration of 400 mg/kg than 200 mg/kg. Conclusion: Pharmacognostic characteristics and phytochemical properties revealed in this study could be used for the pharmacopoeial standard. Ethyl acetate extract showed potent antioxidant and analgesic activity.